Blunt chest trauma – An audit of injuries diagnosed by the MDCT examination - Turkalj, Ivan; Petrović, Kosta; Stojanović, Sanja; Petrović, Djorđe; Brakus, Alma; Ristić, Jelena (Vojnosanitetski pregled, 2014)
Background/Aim. Multidetector computed tomography (MDCT) characterised by speed and precision is increasingly accessible in emergency wards. The aim of our study was to determine the most common injuries to the chest region, as well as type associated extrathoracic injuries, and the treatment outcome. Methods. This prospective study included 61 patients with blunt trauma who were submitted to computed tomography (CT) of the thorax. The number of injuries was evaluated by organs and organ systems of the chest. The cause of the injury, the length and the outcome of the treatment, and the presence of injuries in other regions were assessed. Results. Chest injuries were associated with injuries to other regions in 80.3% cases, predominantly injuries to extremities or pelvic bones in 54.1% cases, followed by head injuries in 39.3% patients. Associated thoracic injuries were present in 90.9% of patients with lethal outcome. Lung parenchymal lesions, pleural effusions and rib fractures were the most common injuries affecting 77.1%, 65.6% and 63.9% of the cases, respectively. Conclusion. Blunt chest trauma is a significant problem affecting predominantly males in their forties and it is usually caused by a motor vehicle accident. In case of pneumomediastinum or mediastinal haematoma, the use of 3D reconstructions is advised for diagnosing possible tracheobronchial ruptures and thoracic aorta injuries. Increased resolution of CT scanners yielded a large number of findings that are occult on radiography, especially in the event of lung parenchymal and pleural injuries. However, none imaging modality can replace surgical judgement.